2016
DOI: 10.1038/leu.2016.265
|View full text |Cite
|
Sign up to set email alerts
|

Copy-number analysis identified new prognostic marker in acute myeloid leukemia

Abstract: Recent advances in genomic technologies have revolutionized acute myeloid leukemia (AML) understanding by identifying potential novel actionable genomic alterations. Consequently, current risk stratification at diagnosis not only relies on cytogenetics, but also on the inclusion of several of these abnormalities. Despite this progress, AML remains a heterogeneous and complex malignancy with variable response to current therapy. Although copy-number alterations (CNAs) are accepted prognostic markers in cancers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 39 publications
4
35
0
Order By: Relevance
“…Consistent with a previous report [9], this study showed that CNVs were not randomly distributed in the chromosomes. Ampli cations were more frequent in chromosomes 1,8,19, 21, and 22 of the TARGET cohort and TCGA cohorts, and deletions were more frequent in chromosomes 7, 16, and X.…”
Section: Distribution Of the Cnvsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with a previous report [9], this study showed that CNVs were not randomly distributed in the chromosomes. Ampli cations were more frequent in chromosomes 1,8,19, 21, and 22 of the TARGET cohort and TCGA cohorts, and deletions were more frequent in chromosomes 7, 16, and X.…”
Section: Distribution Of the Cnvsupporting
confidence: 93%
“…The array data were used on CNV analysis in previous AML studies [9,[15][16][17]. In this study, we used GWS data from TARGET to discover valuable CNV markers and validated them with the array data from TCGA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high copy number of oncogenes has been reported in some leukemia patients. 47 The situation in the retroviral system may mimic such leukemia cases. The gene dose has some effects on the transformation efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies had shown that high expression of ERG and ERG amplification, the most frequent copy-number alteration (CNA), are all the worse prognostic markers in AML patients [5, 6, 33]. ETS2, one of the members of the ETS family as ERG, was previously characterized as a proto-oncogene in AMKL children that is Down-syndrome and non-Down-syndrome-related [10], but the expression and clinical prognosis of ETS2 in AML remains unknown.…”
Section: Discussionmentioning
confidence: 99%